Street child - Doherty, Berlie (London : HarperCollins Children's, 2009)
Unforgettable tale of an orphan in Victorian London, based on the boy whose plight inspired Dr Barnardo to found his famous children's homes.
Originally published in print: 1995.
Keywords: Homeless persons -- Juvenile fiction